Electrical resistivity of Si3N4 ceramics with Yb2O3 additive. Issue 3 (19th November 2021) - Yahagi, Tsukaho; Kawai, Daisuke; Takahashi, Takuma; Iijima, Motoyuki; Tatami, Junichi
Abstract: Si3 N4 ceramics with excellent mechanical properties are used for heat dissipation substrates and so on. In order to improve their reliability and expand their application fields, it is desirable to understand and control the electrical properties of Si3 N4 ceramics. In this study, the electrical resistivity of Si3 N4 ceramics with Yb2 O3 additive was investigated by applying various voltages at temperatures ranging from 25°C to 300°C. When Yb2 O3 was added as a sintering aid to Si3 N4 ceramics, a crystalline J‐phase (Yb4 Si2 O7 N2 ) was formed and their electrical resistivity was significantly lower than that of Y2 O3 additive. The electrical resistivity of the Yb2 O3 ‐added ceramics decreased with an increase in temperature and applied voltage. Yb existed in multiple valence states, Yb 2+ and Yb 3+, in the Si3 N4 ceramics and the decrease in the electrical resistivity can be attributed hopping conduction through the J‐phase. The J‐phase in the Si3 N4 ceramics was observed to be continuous, and percolation analysis suggested that the J‐phase formed an infinite cluster. Therefore, the decrease in the electrical resistivity of the Yb2 O3 ‐added Si3 N4 ceramics was found mainly to result from the formation of an infinite cluster of J‐phase, which exhibits hopping conduction.